Indian Financial System Reform Selected Issues - Schich, Sebastian (OECD Publishing, 2007)
India's financial sector has become much more diversified, with capital markets playing an increasingly important role. These markets have been substantially deregulated and, recent changes notwithstanding, many restrictions on capital flows have been eased, especially with respect to equity inflows. As well, the health of the public banks, which initially had very weak balance sheets, has been restored. While India's regulatory, supervisory and financial policy authorities have made progress, they are likely to face challenges related to several aspects characterising the country's financial system, including its banking sector and its capital markets. Banks remain subject to government imposed constraints on their lending portfolios and the banking sector is still dominated by public institutions. Although the Indian government has intensified its efforts to develop corporate bond markets, the latter remain relatively underdeveloped. Equity markets, which have evolved considerably, have recently been characterised by substantial price increases, in part reflecting large foreign inflows. This development raises the question of sustainability of valuations under changing global monetary liquidity conditions and risk aversion. Different policy responses have been considered by Indian authorities. Representatives from these authorities expressed a reluctance to interfere with the market process. However, the recent decisions by policy authorities suggest that during the course of the ongoing deliberations by policy authorities, these considerations have been outweighed by concerns about the consequences of failing to constrain inflows. The decision by authorities to disallow issuance of "participatory notes" by foreign institutional investors has to be seen in this context
Keywords: Finance and Investment